Integration of Ibn Khaldun’s Islamic Education Thought and the Role of Technology in Realizing Value Based Learning in the Digital Era - Irwan Suwandi; Muhammad Ardiansyah; Moch. Romli (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2025)
In the current era, the development of information and communication technology is progressing rapidly, significantly influencing the field of education, particularly Islamic education. The integration between Islamic values and technology has become an essential necessity to ensure that Islamic education does not fall behind or become overtaken by modernization. This scientific journal aims to examine the thoughts of Islamic education from the perspective of classical Islamic educational philosophy, particularly that of Ibn Khaldun, and to analyze the role of technology as a medium, tool, and instrument of education in the context of digitalization. This study employs a qualitative method through a literature review of relevant classical and contemporary sources. The results of the study show that technology serves as an effective means of transforming Islamic values in alignment with the principles of ethics, Islamic morality, and holistic educational thought according to Ibn Khaldun. Thus, the synergy between Islamic thought and technology can strengthen and accelerate the goals of Islamic education namely, to develop insan kamil (a complete human being) who is faithful, knowledgeable, possesses strong character, and is capable of adapting in this digital era.